2002
DOI: 10.1039/b210163g
|View full text |Cite
|
Sign up to set email alerts
|

Antisense oligonuclotides with oxetane-constrained cytidine enhance heteroduplex stability, and elicit satisfactory RNase H response as well as showing improved resistance to both exo and endonucleasesElectronic supplementary information (ESI) available: RNA cleavage kinetics. See http://www.rsc.org/suppdata/ob/b2/b210163g/

Abstract: Antisense oligonucleotides (AONs) with single and double oxetane C modifications [1',2'-oxetane constrained cytidine, 1-(1',3'-O-anhydro-beta-D-psicofuranosyl)cytosine] have been evaluated, in comparison with the corresponding T-modified AONs, for their antisense potentials by targeting to a 15mer complementary RNA. Although the C modified mixmer AONs show approximately 3 degrees C drop per modification in melting temperature (Tm) of their hybrid AON-RNA duplexes, they are found to be good substrates for RNase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 31 publications
(18 reference statements)
2
45
0
Order By: Relevance
“…15 The authors demonstrated the complex nature of the interactions rigidifying the RNA versus the DNA, suggesting that perhaps high ordered water molecules around the RNA reduce the flexibility of RNA. Similar calculations were later performed by Auffinger and Westhof, 21,22 who compared d(CG) 6 $d(CG) 6 and d(TA) 6 $d(TA) 6 DNAs with the corresponding RNA duplexes, r(CG) 6 $r(CG) 6 and r(UA) 6 $r(UA) 6 . From the analysis of dihedral changes along the sequence and their time fluctuations, DNA was found to be more flexible than RNA.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…15 The authors demonstrated the complex nature of the interactions rigidifying the RNA versus the DNA, suggesting that perhaps high ordered water molecules around the RNA reduce the flexibility of RNA. Similar calculations were later performed by Auffinger and Westhof, 21,22 who compared d(CG) 6 $d(CG) 6 and d(TA) 6 $d(TA) 6 DNAs with the corresponding RNA duplexes, r(CG) 6 $r(CG) 6 and r(UA) 6 $r(UA) 6 . From the analysis of dihedral changes along the sequence and their time fluctuations, DNA was found to be more flexible than RNA.…”
Section: Introductionmentioning
confidence: 80%
“…[1][2][3]5 Indeed, it is known that RNase H recognizes and degrades DNA-RNA hybrids, but it is inactive against RNA-RNA duplexes and other RNA-hybrid molecules, despite the fact that all these duplexes pertain to the A-family. 6,7 More surprisingly, the complex mechanism involving gene silencing by small interference RNAs is activated by duplex RNA, but not by other RNA hybrid duplexes of similar structure. 8,9 Clearly, besides the general helical structure, other properties must be exploited by nature to distinguish between helical structures.…”
Section: Introductionmentioning
confidence: 98%
“…The resulting AON-RNA heterodimers displayed increased stability towards degradation by nucleases. [78] However, it is altogether unclear whether the stability is directly related to the introduction of the oxetane unit itself or merely follows from the unique conformational constraints imposed by the cis-ring fusion.…”
Section: Applications Of Oxetanes In Medicinal Chemistrymentioning
confidence: 99%
“…Another class of 2′-modification is the BNA in which the ribose 2′-oxygen is linked to the 4′-carbon via a methylene bridge as in Locked Nucleic Acid (LNA; Wengel et al, 2001) and carbocyclic-LNA (Srivastava et al, 2007; Bramsen et al, 2009), via an ethylene bridge as in ethylene-bridged nucleic acid (ENA; Hamada et al, 2002) and carbocyclic-ENA (Srivastava et al, 2007; Bramsen et al, 2009), or to the 1′-carbon as in oxetane (OXE; Pradeepkumar et al, 2003; Bramsen et al, 2009). This radical modification type generates nucleotides with interesting properties to siRNA design; The methylene bridge in the very popular LNA-modification locks the sugar moiety in the RNA-helical C3′- endo conformation, which additively increase RNA duplex thermostability by 2–10°C per LNA (Petersen and Wengel, 2003).…”
Section: Tools For Chemical Modification Of Sirnasmentioning
confidence: 99%